An Alternative Stability Pact for the European Union - Philip Arestis; Kevin McCauley; Malcolm Sawyer (Levy Economics Institute of Bard College, 2000)
This paper proposes an alternative stability and growth pact among European Union (EU) governments that would underpin the introduction of a single currency and a "single market" within the EU. The alternative pact embraces a number of new aspects of integration within the EU that are based on a different monetary analysis (different from that of "new monetarism"), new objectives for economic policy (such as employment and growth), and new institutions to reduce various kinds of disparities across the EU. The paper begins by critically examining the Stability and Growth Pact, which accompanied the introduction of the euro in January 1999, but which has not received as much attention in the policy debates on the euro as some other aspects of it. This is followed by a discussion of the institutional underpinnings of the euro, with the argument made that the institutional arrangements have a number of weaknesses. An alternative pact governing monetary and fiscal policy, which contains the promotion of the objective of full employment and that requires the creation of new institutions, is proposed.
Keywords: 330